Confronting dental uncertainty in old age. (February 2014) - MacEntee, Michael I.; Mathu‐Muju, Kavita R.
Abstract : Objective: To provide an overview of the literature about uncertainty in health care and how it relates to the oral health care of older people. Background: The medical literature describes uncertainty in health care from the initial informed‐consent to its impact on a patient's ability to cope with undesirable outcomes. Methods: A narrative review of the medical, dental and psychological literature was conducted to identify pertinent information on the theory and implications of uncertainty in healthcare. The findings are infused into a case‐report illustrating the recurrence of uncertainty experienced by an older woman who had multiple treatments over several years to restore her dentition damaged severely by dental caries. Results: Uncertainty originates from inadequate understanding, incomplete information and undifferentiated alternatives leading to unnecessary diagnostic tests and healthcare costs. A conceptual taxonomy clarifies the characteristics of uncertainty in the context of scientific, practical or personal sources and offers management possibilities through effective communications to identify choices and probabilities that help patients to adapt and cope with adverse events. Conclusions: Uncertainty pervades healthcare. It can lead patients to self‐blame, anger and withdrawal from care unless it is communicated effectively so that they can adapt and cope with the disappointment of adversity and continue with alternative approaches to care.